2014
DOI: 10.1159/000365573
|View full text |Cite
|
Sign up to set email alerts
|

Resistant Palmoplantar Lesions in Patients of Psoriasis: Evaluation of the Causes and Comparison of the Frequency of Delayed-Type Hypersensitivity in Patients without Palm and Sole Lesions

Abstract: Objective: To examine the reasons for resistance to treatment in cases of palmoplantar psoriasis, and also to compare the frequency of delayed-type hypersensitivity to common sensitizers with those cases of psoriasis without palmoplantar involvement. Subjects and Methods: One hundred and three patients with resistant palmoplantar psoriasis were examined for a possible drug reaction, fungal infection or contact allergy. Patch testing was done for another 100 patients with psoriasis vulgaris without palm and sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…ACD reactions in palmoplantar localisation are often chronic and due to the ubiquitous character of allergens not self-limited. Persistent ACD acts as a negative determinant of psoriasis (5). Allergy diagnostic including patch testing is essential for the correct diagnosis, successful treatment and, in our opinion, mandatory in cases of palmoplantar psoriasis.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…ACD reactions in palmoplantar localisation are often chronic and due to the ubiquitous character of allergens not self-limited. Persistent ACD acts as a negative determinant of psoriasis (5). Allergy diagnostic including patch testing is essential for the correct diagnosis, successful treatment and, in our opinion, mandatory in cases of palmoplantar psoriasis.…”
Section: Discussionmentioning
confidence: 95%
“…However, there are conflicting results regarding the correlation of psoriasis and contact sensitivity. Some authors have observed an inverse relationship (4), while others have reported a higher incidence of type IV sensitization only in palmoplantar psoriasis (5,6). Another study noted a positive correlation with the duration of the disease, but not with the site of lesions (7).…”
mentioning
confidence: 99%
“…Palmoplantar psoriasis is more challenging to treat than psoriasis in other skin areas. The use of topical therapies, ultraviolet phototherapy, oral retinoids, methotrexate or anthralin often results in inadequate treatment results . Newer small molecules and biologics have increased the possibility of effective treatment, but the evidence for this is limited and often from short‐term studies .…”
mentioning
confidence: 99%
“…81 Also, the use of several topics in resistant lesions can make the patient susceptible to contact hypersensitivity. 82 Therefore, topic treatments should be the preferred approach in a patient with PPP. However, many patients end up, eventually requiring treatment with systemic drugs, which present risks of side effects that may restrict their use in clinical practice.…”
Section: Treatmentmentioning
confidence: 99%